Konsep Dasar Adh-Dhaman (Penjaminan) - Rizki Eliana; Musyrifah Salmi; Fatmah Taufik Hidayat (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Adh-dhaman is an essential concept in Islamic law, particularly related to liability and obligations for damages or harm caused by an individual to the property or rights of others. The term originates from the Arabic word dhimmah, which means responsibility or obligation, and has broad applications in the context of muamalah (social and business interactions). The legal basis for Adh-dhaman in Islamic law is found in both the Qur'an and the sayings of Prophet Muhammad (peace be upon him). In the Qur'an, Allah says, "And do not consume one another’s wealth unjustly" (Surah Al-Baqarah: 188). This reflects the principle that no one should unlawfully take the rights of others, and if they do, they are obligated to make restitution. In the hadith, the Prophet (peace be upon him) said, "There should be neither harming nor reciprocating harm" (Narrated by Ibn Majah). This hadith emphasizes that in Islam, any act that causes harm to others, whether directly or indirectly, must be accounted for. Adh-dhaman involves two primary elements: sabab (cause) and dhaman (compensation). In every case, Islamic law considers the intention and the degree of negligence to determine whether a person is obligated to compensate and the extent of that compensation.